2017
DOI: 10.21873/invivo.11086
|View full text |Cite
|
Sign up to set email alerts
|

Rebiopsy of Histological Samples in Pretreated Non-small Cell Lung Cancer: Comparison Among Rebiopsy Procedures

Abstract: Abstract. Aim Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) accounts for approximately 80% of lung cancers, and the majority are already unresectable and metastatic upon their initial diagnosis. Cytotoxic chemotherapies such as platinum-based regimens were once the primary therapeutic option for metastatic NSCLC, but their advancement has reached a plateau. Molecular-targeted therapies have been recently developed, and they have provided a remarkable be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Recently, several reports reflecting the reality in different countries have been published. 8,22,[24][25][26] Most studies reported a high re-biopsy success rate, ranging from 75% to 97%, 6,7,9,11 similar to the results of our study. The rebiopsy complication rate is reported to be 1.3-5.8%, 10,11 which is similar to that of initial lung biopsy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Recently, several reports reflecting the reality in different countries have been published. 8,22,[24][25][26] Most studies reported a high re-biopsy success rate, ranging from 75% to 97%, 6,7,9,11 similar to the results of our study. The rebiopsy complication rate is reported to be 1.3-5.8%, 10,11 which is similar to that of initial lung biopsy.…”
Section: Discussionsupporting
confidence: 91%
“…However, re‐biopsy is still challenging in real world clinical practice because of its invasiveness and the different medical environments found in different countries. Recently, several reports reflecting the reality in different countries have been published . Most studies reported a high re‐biopsy success rate, ranging from 75% to 97%, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In treatment strategies based on recent developments in mutation research in NSCLC, re-biopsy has become essential for investigating the tolerance mechanism of a progressed tumor after the initial TKI therapy [ 15 ]. At present, however, re-biopsy is performed only in selected cases in which disease lesions are easily accessible using conventional methods of biopsy [ 16 , 17 ]. It is not clear whether re-biopsy could be applied as a standard technique in all cases of disease progression after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%